Choosing the right strategy for hotel international expansion - Vesna Milovanović; Snežana Milićević (Mенаџмент у хотелијерству и туризму, 2013)
Modern business environment creates new trends, not only on a global level but also on the level of individual enterprises. The accent used to be on the internationalization of production processes and sale of raw materials and final goods, however the internationalization of services is gaining on importance nowadays. The subject of this paper is an analysis of the particularity of hotel business and the key factors influencing hotel performance. The aim is to identify optimal strategies for hotel international expansion under given conditions. Selection of inappropriate strategy for international expansion could be dangerous for hotel success on international market and could make serious losses. This paper is therefore especially valuable to hotels which do not have any experience in international expansion.